O ensino de astronomia no ensino fundamental : percepção e saberes docentes para a formação de professores - Buffon, Alessandra Daniela (2016)
The research has as its central point to understand the importance that teachers assign to Astronomy Teaching in Primary Education, as well as understand the teachers necessary knowledge that allow them to face the challenges of school / academic every day. Thus, it is established key questions of concerns and problems like: "What is the importance of Astronomy in school?" And "What is needed to expand the Astronomy in the classroom?" These questions try to be matched by detecting the importance of the necessary knowledge of teacher and also of its understanding which in tum possibly will expand the Astronomy Teaching in the classroom. In order to answer these questions the interlocutors of the research are teachers of the discipline of Sciences (Brazil) / Physical chemistry (Portugal) and researchers at the teacher training area of Astronomy Teaching countries of Brazil and Portugal. The methodology used for data collection and analysis governs phenomenological principles, since the stories of life and formation are constituted as an approach to hermeneutics research methodologies. The data was collected through discourses recorded on video. The analysis of the data was divided into categories so that the phenomenon could be identified. The present study intends to point out the need for a reflection on the relationship between teacher education and the Astronomy Teaching dialogue with Langhi and Nardi (2012); Tardif (2007); among others. As a result it can be seen that the importance of astronomy for teaching is established by five aspects: the content related to the topic; curiosity; the taste of the student; interest in science; and cultural issues. To expand Astronomy role play in the classroom is necessary to pay attention also to five notes: reports of experience; the improvement and teacher training; teaching resources; the extension of time; and experimental and extracurricular activities. It is concluded that to achieve quality education for students is necessary to give voice to teachers facing the challenges of introducing astronomy every day in schools, opposing his discourses with researchers in this field, strengthening the relationship between universities and schools in order to create opportunities for continued education facing the emerging needs of teachers.